Functions of microRNA-143 in the apoptosis, invasion and migration of nasopharyngeal carcinoma - Chen, Jin-Hui (Exp Ther Med, 2016)
Nasopharyngeal carcinoma (NPC) is a common cancer characterized by poor prognosis in areas of Southern China where it is endemic. microRNAs (miRNAs) are a class of naturally occurring small noncoding RNAs, some of which contribute to the initiation and development of cancer. The current study was designed to examine the expression level of miR-143 in NPC tissues. The potential functional targets of miR-143 involved in tumor apoptosis, invasion and migration were also investigated. Reverse transcription-quantitative polymerase chain reaction was used to evaluate the expression levels of miR-143 in clinical NPC specimens. Western blotting was used to explore the expression levels of extracellular signal regulated kinase (ERK)-5, Kirsten rat sarcoma viral oncogene homolog (KRAS), caspase 3 and B-cell lymphoma 2 (Bcl-2) in CNE-2Z cells following transfection with miR-143. Significantly decreased expression levels of miR-143 were observed in NPC tissues in comparison with matched normal nasopharyngeal tissues. Moreover, negative associations of miR-143 with tumor invasion depth, as well as lymph node metastasis were found. The enforced expression of miR-143 induced NPC cell apoptosis in addition to the suppression of growth, migration and invasion. The functions of miR-143 in NPC are mediated, at least in part, by the inhibition of ERK-5 activity and promotion of caspase 3 and KRAS expression. These findings suggest that miR-143 may function as a tumor suppressor in the development and progression of NPC.